History of Trauma Exposure, Post-Traumatic Stress Disorder (PTSD), with Comorbid Depression and Resilience among Students of Higher Educational Institutions in Sarawak - Kokilah, Manogaran (Universiti Malaysia Sarawak (UNIMAS), 2021)
Research on history of trauma exposure among university students are limited world widely and almost none in Malaysia. The objective of this study is to investigate a history of trauma exposure, PTSD, depressive symptoms and resilience among young adult students in our local higher education institutions. The present study adopts a cross sectional research design and convenient sampling was used in this study. There were 712 university students participated in this study (age ranged from 18 to 27 years old). They were students from private universities and colleges in Sarawak where 57.7% were females and 42.3% were males. Participants was briefed regarding confidentiality and their rights as participants were clarified. Life Events Checklist measured history of trauma exposure, PTSD Checklist -5 measured PTSD symptoms, Centre for Epidemiologic Studies Depression Scale measured symptoms of depression, and Connor-Davidson Resilience Scale was used to measure resilience. Results showed that almost 90% (N = 640) of participants in this study has reported at least one or more trauma exposure. The most prevalent for total trauma exposure were transportation accident (62.5%), death of immediate family member or significant one (42.4%), natural disaster (37.8%), and physical assault (37.2%). Descriptive analysis found that 69 (9.7%) participants reported PTSD symptoms and 130 (18.3%) participants reported depressive symptoms. Female participants reported more PTSD and depressive symptoms than male participants. Participants who suffered from PTSD tend to suffer from depressive symptoms as well and those who reported higher number of trauma exposure, tend to report more PTSD and depressive symptoms. CD-RISC mean score in this study was 59.71 and male participants reported significantly more resilience score than female participants. Participants who exhibited depressive symptoms scored lower resiliency than those without depression symptoms. Regression analysis showed resilience is not a significant predictor for academic performance in general and among those with PTSD or depressive symptoms. Participants who exhibited PTSD symptoms scored lower CGPA than those without PTSD symptoms. Discussion and finding’s implication were presented in relation to variables studies, clinical practices and research. Several suggestions and recommendations were also underlined in order to improve future research. In conclusion prevention and intervention is crucial in addressing mental health concerns among students in higher education institutions.